Structural basis of GABARAP-mediated GABAA receptor trafficking and functions on GABAergic synaptic transmission - Jin Ye (Nature Portfolio, 2021)
The GABARAP protein is known to support the stability of GABAA receptors (GABAARs) in synapses, but the underlying molecular mechanisms remained to be elucidated. Here authors use biochemistry, X-ray crystallography and electrophsyiology and show that GABARAP directly binds to a previously unappreciated region in the γ2 subunit of GABAAR.